Trial by Farce A Dozen Medieval French Comedies in English for the Modern Stage - Enders, Jody (University of Michigan Press, 2023)
Was there more to comedy than Chaucer, the Second Shepherds' Play, or Shakespeare? Of course! But, for a real taste of medieval and Renaissance humor and in-your-face slapstick, one must cross the Channel to France, where over two hundred extant farces regularly dazzled crowds with blistering satires. Dwarfing all other contemporaneous theatrical repertoires, the boisterous French corpus is populated by lawyers, lawyers everywhere. No surprise there. The lion's share of mostly anonymous farces was written by barristers, law students, and legal apprentices. Famous for skewering unjust judges and irreligious ecclesiastics, they belonged to a 10,000-member legal society known as the Basoche, which flourished between 1450 and 1550. What is more, their dramatic send-ups of real and fictional court cases were still going strong on the eve of Molière, resilient against those who sought to censor and repress them. The suspenseful wait to see justice done has always made for high drama or, in this case, low drama. But, for centuries, the scripts for these outrageous shows were available only in French editions gathered from scattered print and manuscript sources. In Trial by Farce, prize-winning theater historian Jody Enders brings twelve of the funniest legal farces to English-speaking audiences in a refreshingly uncensored but philologically faithful vernacular. Newly conceived as much for scholars as for students and theater practitioners, this repertoire and its familiar stock characters come vividly to life as they struggle to negotiate the limits of power, politics, class, gender, and, above all, justice. Through the distinctive blend of wit, social critique, and breathless boisterousness that is farce, we gain a new understanding of comedy itself as form of political correction. In ways presciently modern and even postmodern, farce paints a different cultural picture of the notoriously authoritarian Middle Ages with its own vision of liberty and justice for all. Theater eternally offers ways for new generations to raise their voices and act.